A Lower Bound on the Critical Momentum of an Impurity in a Bose–Einstein Condensate - Hinrichs, Benjamin; Lampart, Jonas (Comptes Rendus. Mathématique)

On Lieb–Robinson Bounds for a Class of Continuum Fermions - Hinrichs, Benjamin; Lemm, Marius; Siebert, Oliver (Annales Henri Poincaré)

Non-Fock ground states in the translation-invariant Nelson model revisited non-perturbatively - Hasler, David; Hinrichs, Benjamin; Siebert, Oliver (Journal of Functional Analysis)
Keywords: Analysis

ADMM-TGV image restoration for scientific applications with unbiased parameter choice - Zietlow, Christian; Lindner, Jörg (Numerical Algorithms)

Ruelle-Taylor resonances of Anosov actions - Weich, Tobias; Guedes Bonthonneau, Yannick; Guillarmou, Colin; Hilgert, Joachim (J. Europ. Math. Soc.)

Non-rotationally symmetric joints – Mechanisms and load bearing capacity - Devulapally, Deekshith Reddy; Martin, Sven; Tröster, Thomas (Materials Research Proceedings)
Abstract. Traditionally, joints are cylindrical and rotationally symmetric. In the present study, non-rotationally symmetric joints are used for joining steel and Glass mat-reinforced thermoplastic sheets (GMT). In addition, the study also analyzes the impact of non-rotational symmetric joint rotation on the load-bearing capacity. Single lap joint specimens were fabricated using the In-Mold assembly technique for joining steel sheets with GMT. Tensile shear tests were performed on different orientations of the joint geometry, and it was observed that changing the joint orientation influences the load-bearing capacity. The joints are constitutively modeled using beam elements and the influence of joint rotation on load distribution is examined through a static simulation study.

“I Guess this is Growing Up” Analysis of Pop-Punk’s Regained Popularity and Its Shift From Bands to Personas. - Ruth, Nicolas; Jacke, Christoph (Persona Studies)
This research article examines the transformation of pop-punk from bands to solo artists and how the genre regained popularity due to new popular personalities and the transmedia engagement in social media and with established media. Through a three-pronged approach, this studyadopts phenomenological, theoretical, and empirical perspectives to understand the transition and regained popularity fully. The phenomenological angle delves into the case studies of musicians, revealing key factors behind the shift to solo artists in pop-punk. Theoretical explanations contextualize the phenomenon within broader cultural frameworks, considering industry and transmedia dynamics, audience preferences, and technological advancements. Empirical evidence, including statistical data from socialmedia profiles, quantifies the impact of the shift.This study contributes to a comprehensive understanding of pop-punk's transformation, offering an exploration of its past, present, and future within the ever-evolving music industries and transmedia landscapes
Keywords: Pop-punk; Popular Musical Personas; Solo Artists; SocialMedia; Transmedia; TikTok

Stars, Anti-Stars, Anti-Star-Stars. Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions. - Jacke, Christoph (Persona Studies)
The phenomenon of stars and celebrities in media cultures – and especially in popular music cultures – seems to be omnipresent. At the same time, there is an astounding lack of analysis and research on these media personalities and personas, and international celebrity studies only recently a developing new field. Similarly, these kinds of observations are still very rare especially in German sociology as well as communication, media, culture and popular music studies. In this article, I therefore want to concentrate on the foundations of studying stars and celebrities within the attention economies by undertaking a theoretical transmedia-cultural framing of media personas and suggesting a typology. This ensuing typology of stars, anti-stars, and anti-star stars – especially within popular music cultures – demonstrates how stars and celebrities and their quantities and qualities of success and peer-group specific values coming form programs of (media and music) culture can serve as persona-seismographs of socio-cultural change between tradition and innovation
Keywords: Stars; Celebrities; Popular Music; Transmedia Culture; Personas

"Heute Disco, morgen Umsturz, übermorgen Landpartie" - Kurze Anmerkungen zu Pop-Gipfeln. - Jacke, Christoph
Keywords: Popmusic; culture; politics; Förderung; Forschung

Towards a BFO-based ontology of understanding in explanatory interactions - Booshehri, Meisam; Buschmeier, Hendrik; Cimiano, Philipp (Proceedings of the 4th International Workshop on Data Meets Applied Ontologies in Explainable AI (DAO-XAI))
This work takes steps towards situating the concepts relevant to explanation and understanding in explanatory interactions within the scope of Basic Formal Ontology. We introduce novel ontological accounts of understanding and explanation in BFO-terms, which foster a shared conceptualization of explanations and explainee's understanding during explainer-explainee interactions. This approach also enables the tracking of different aspects of understanding and explanation through cognitive profiling of various measurable aspects under the heading of process profile in BFO. Additionally, we differentiate between the private mental process of understanding and understanding displays. Finally, we characterize the relationship between understanding displays and explanations.

Detecting subtle differences between human and model languages using spectrum of relative likelihood - Xu, Yang; Wang, Yu; An, Hao; Liu, Zhichen; Li, Yongyuan (Proceedings of the 2024 Conference on Empirical Methods in Natural Language Processing)
Human and model-generated texts can be distinguished by examining the magnitude of likelihood in language. However, it is becoming increasingly difficult as language model's capabilities of generating human-like texts keep evolving. This study provides a new perspective by using the relative likelihood values instead of absolute ones, and extracting useful features from the spectrum-view of likelihood for the human-model text detection task. We propose a detection procedure with two classification methods, supervised and heuristic-based, respectively, which results in competitive performances with previous zero-shot detection methods and a new state-of-the-art on short-text detection. Our method can also reveal subtle differences between human and model languages, which find theoretical roots in psycholinguistics studies.

Conversational feedback in scripted versus spontaneous dialogues: A comparative analysis - Pilán, Ildikó; Prévot, Laurent; Buschmeier, Hendrik; Lison, Pierre (Proceedings of the 25th Meeting of the Special Interest Group on Discourse and Dialogue)
Scripted dialogues such as movie and TV subtitles constitute a widespread source of training data for conversational NLP models. However, there are notable linguistic differences between these dialogues and spontaneous interactions, especially regarding the occurrence of communicative feedback such as backchannels, acknowledgments, or clarification requests. This paper presents a quantitative analysis of such feedback phenomena in both subtitles and spontaneous conversations. Based on conversational data spanning eight languages and multiple genres, we extract lexical statistics, classifications from a dialogue act tagger, expert annotations and labels derived from a fine-tuned Large Language Model (LLM). Our main empirical findings are that (1) communicative feedback is markedly less frequent in subtitles than in spontaneous dialogues and (2) subtitles contain a higher proportion of negative feedback. We also show that dialogues generated by standard LLMs lie much closer to scripted dialogues than spontaneous interactions in terms of communicative feedback.

Turn-taking dynamics across different phases of explanatory dialogues - Wagner, Petra; Włodarczak, Marcin; Buschmeier, Hendrik; Türk, Olcay; Gilmartin, Emer (Proceedings of the 28th Workshop on the Semantics and Pragmatics of Dialogue)
We examined the turn-taking dynamics across different phases of explanatory dialogues, in which 21 different explainers explained a board game to 2–3 explainees each. Turn-taking dynamics are investigated focusing on >19K floor transitions, i.e., the detailed patterns characterizing turn keeping or turn yielding events (Gilmartin et al., 2020). The explanations were characterized by three different phases (board game absent, board game present, interactive game play), for which we observed differences in turn-taking dynamics: explanations where the board game is absent are characterized by less complex floor transitions, while explanations with a concretely shared reference space are characterized by more complex floor transitions, as well as more floor transitions between interlocutors. Also, the speakers’ dialogue role (explainer vs. explainee) appears to have a strong impact on turn-taking dynamics, as floor transitions that do not conform with the dialogue role tend to involve more effort, or floor management work.

Revisiting the phenomenon of syntactic complexity convergence on German dialogue data - Wang, Yu; Buschmeier, Hendrik (Proceedings of the 20th Conference on Natural Language Processing (KONVENS 2024))
We revisit the phenomenon of syntactic complexity convergence in conversational interaction, originally found for English dialogue, which has theoretical implication for dialogical concepts such as mutual understanding. We use a modified metric to quantify syntactic complexity based on dependency parsing. The results show that syntactic complexity convergence can be statistically confirmed in one of three selected German datasets that were analysed. Given that the dataset which shows such convergence is much larger than the other two selected datasets, the empirical results indicate a certain degree of linguistic generality of syntactic complexity convergence in conversational interaction. We also found a different type of syntactic complexity convergence in one of the datasets while further investigation is still necessary.

How much does nonverbal communication conform to entropy rate constancy?: A case study on listener gaze in interaction - Wang, Yu; Xu, Yang; Skantze, Gabriel; Buschmeier, Hendrik (Findings of the Association for Computational Linguistics ACL 2024)
According to the Entropy Rate Constancy (ERC) principle, the information density of a text is approximately constant over its length. Whether this principle also applies to nonverbal communication signals is still under investigation. We perform empirical analyses of video-recorded dialogue data and investigate whether listener gaze, as an important nonverbal communication signal, adheres to the ERC principle. Results show (1) that the ERC principle holds for listener gaze; and (2) that the two linguistic factors syntactic complexity and turn transition potential are weakly correlated with local entropy of listener gaze.

Disentangling Dialect from Social Bias via Multitask Learning to Improve Fairness - Spliethöver, Maximilian; Menon, Sai Nikhil; Wachsmuth, Henning (Findings of the Association for Computational Linguistics: ACL 2024)
Dialects introduce syntactic and lexical variations in language that occur in regional or social groups. Most NLP methods are not sensitive to such variations. This may lead to unfair behavior of the methods, conveying negative bias towards dialect speakers. While previous work has studied dialect-related fairness for aspects like hate speech, other aspects of biased language, such as lewdness, remain fully unexplored. To fill this gap, we investigate performance disparities between dialects in the detection of five aspects of biased language and how to mitigate them. To alleviate bias, we present a multitask learning approach that models dialect language as an auxiliary task to incorporate syntactic and lexical variations. In our experiments with African-American English dialect, we provide empirical evidence that complementing common learning approaches with dialect modeling improves their fairness. Furthermore, the results suggest that multitask learning achieves state-of-the-art performance and helps to detect properties of biased language more reliably.

What you need to know about a learning robot: Identifying the enabling architecture of complex systems - Beierling, Helen; Richter, Phillip; Brandt, Mara; Terfloth, Lutz; Schulte, Carsten; Wersing, Heiko; Vollmer, Anna-Lisa (Cognitive Systems Research)
Nowadays we deal with robots and AI more and more in our everyday life. However, their behavior is not always apparent to most lay users, especially in error situations. This can lead to misconceptions about the behavior of the technologies being used. This in turn can lead to misuse and rejection by users. Explanation, for example through transparency, can address these misconceptions. However, explaining the entire software or hardware would be confusing and overwhelming for users. Therefore, this paper focuses on the ‘enabling’ architecture. It describes those aspects of a robotic system that may need to be explained to enable someone to use the technology effectively. Furthermore, this paper deals with the ‘explanandum’, i.e. the corresponding misunderstandings or missing concepts of the enabling architecture that need to be clarified. Thus, we have developed and are presenting an approach to determine the ‘enabling’ architecture and the resulting ‘explanandum’ of complex technologies.
Keywords: Robotics HRI Explainability Didactics Didactic reconstruction

Advancing Human-Robot Collaboration: The Impact of Flexible Input Mechanisms - Beierling, Helen; Loos, Kira; Helmert, Robin; Vollmer, Anna-Lisa
This position paper calls for an increase in the number and flexibility of input mechanisms in user-robot in- teractions, highlighting their potential to enhance learning algo- rithms through user feedback. Moreover, we argue that refining interfaces, interactions, and systems is crucial for the optimal integration of mechanisms into learning processes. Our call to research involves the development of interfaces that enable flexible mechanisms, and the mechanisms interactions can benefit most from, and the algorithmic incorporation of user input. This aims to advance the adaptability and responsiveness of robotic systems in human-centric environments

Inferring Partner Models for Adaptive Explanation Generation - Robrecht, Amelie; Buhl, Heike M.; Kopp, Stefan (Proceedings of the 28th Workshop on the Semantics and Pragmatics of Dialogue)

Task-specific scan trajectory modification for dimensional X-ray computed Tomography with high throughput - Butzhammer, Lorenz; Hausotte, Tino (tm - Technisches Messen)